Implementasi Chatbot Deteksi Depresi Dini Pada Mahasiswa Dengan Phq-9 (Patient Health Questionnaire) Menggunakan NLP (Natural Language Processing). - Muhammad Najamuddin Dwi Miharja; Shohibul Adhkar (Prosiding Sains dan Teknologi, 2022)
One of the serious problems in public health according to the World Health Organization (WHO) is depression. According to WHO depression ranks fourth disease in the world. When someone experiences depression, it will have an impact on reduced productivity, especially for students. The Patient Health Questionnaire (PHQ-9) is a sequence of questions in the initial screening of depression to see the initial severity of depression. Chatbots are applications with artificial intelligence that can communicate with humans. Natural Language Processing is one of the subtopics of Artificial Intelligence, which is an application that can have the advantage of understanding human language normally. In this study, a chatbot service was implemented for Early Detection of Depression in Students with PHQ-9 (Patient Health Questionnaire) using NLP (Natural Language Processing). It was found that around 84% answered that chatbots can help for early detection of depression. Keywords: Chatbot, Natural language Processing (NLP), PHQ-9